Geometric Analysis of the Wantilan – Cipeundeuy Road Segment - Aditya, Tandhang Penta; Trijayanti, Wiwin; Widyadhana, Gibran Arya; Isradi, Muhammad; Nabila, Nabila (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The development of rural areas into sub-district regions in Subang Regency necessitates improvements in transportation infrastructure to support community mobility and agricultural product distribution. One important road segment that requires development is the Wantilan – Cipeundeuy Sub-district. This study aims to analyze the conformity of road geometric design based on the Road Geometric Design Guidelines (PDGJ, 2021), determine pavement layer thickness according to the Pavement Design Manual (MDP, 2024), and estimate construction cost requirements. The methods employed include primary and secondary data collection, geometric analysis, pavement design analysis, and cost estimation. Field data indicate that the 2 km road segment contains three main horizontal curves with a design speed of 80 km/h and a superelevation value of 6%. The calculation results show a curve radius of 252 meters with deflection angles ranging from 3,69˚ to 5,54˚, which comply with thw requirements of PDGJ 2021. The subgrade soil has a California Bearing Ratio (CBR) value of 6,5%, classified as medium bearing capacity soil. The pavement structure design consists of an HRS-BC surface layer, a 200 mm Class A aggregate base course, and a 200 mm Class A aggregate subbase course. The design life of the road is set at 12 years with an average annual rainfall of 1,500 – 1,800 mm. Based on the analysis results, the proposed geometric conditions and pavement design meet technical standards and are feasible to improve road user comfort and safety.